"Impact Of Festivities On Biochemical Oxygen Demand (BOD) In The Yamuna River" - Ms. Anita Khosla; Ms.Deepti Sharma (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2025)
The Yamuna River, often called the lifeline of North India, suffers from severe pollution, significantly impacting its ecological and human health. One of the primary indicators of pollution in the Yamuna is the Biochemical Oxygen Demand (BOD), a measure of organic matter in the water.The Yamuna Action Plan (YAP) is a bilateral project between India and Japan to improve the quality of water in Yamuna River.The YAP has been implemented in multiple phases i.e., YAP-I, YAP-II, and YAP-III. Despite significant financial investments in the phases of Yamuna Action Plan (YAP-I, YAP-II, and YAP-III) by the Delhi government and other stakeholders, the water quality of the Yamuna River remains critically poor. This paper examines the causes and implications of elevated BOD levels in the Yamuna and proposes a comprehensive action plan to reduce these levels. The study focuses on scientific, policy-driven, and community-oriented strategies for sustainable river rejuvenation.